Analysis of the Impact of the Raskin Program on Food Security for Poor Households in Indonesia - Mustofa, Mustofa; Sugiyanto, Catur; Susamto, Akhmad Akbar (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2023)
This study aims to determine the impact of assistance from the rice program for people experiencing poverty on food security for poor households. The data in this paper are sourced from the fourth (2007) and fifth (2014) Indonesian Family Life Survey (IFLS). A total of 1346 household samples were used in this study. The sample consisted of 401 treatment groups and 945 control groups. The treatment group is poor households that receive Raskin assistance, and the control group is poor households that do not receive Raskin assistance. The analysis used is Propensity Score Matching (PSM) with Difference in Difference (DiD). The study's results prove that the Rice for the Poor program has no significant impact on the proportion of household food expenditure. The interaction between the variables year (after) and treatment (Raskin) has no significant effect on the proportion of household food. The provision of the Raskin program in a longitudinal period has no impact on household per capita food expenditure.